2013
DOI: 10.1002/pds.3431
|View full text |Cite
|
Sign up to set email alerts
|

Association of potentially inappropriate medication use with patient and prescriber characteristics in Medicare Part D

Abstract: Purpose The use of potentially inappropriate medications (PIMs) in older people is associated with increased risk of adverse drug events and hospitalization. This study aimed to determine the contribution of primary prescribers to variation in PIM use. Methods This was a retrospective cohort study using 2008 Medicare Part D event files and claims data for a 100% sample of Texas beneficiaries. PIM use was defined as receiving any of 48 medications on the Beers 2003 list of PIMs. Patient characteristics associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
71
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 30 publications
(32 reference statements)
8
71
1
2
Order By: Relevance
“…In addition, approximately 30% of members who did not meet the definition of PIM use at the time of initiation of an antimuscarinic OAB treatment had medication use or a diagnosis that would be considered indicative of PIM use after initiation of OAB antimuscarinic treatment, demonstrating the dynamic nature of medication regimens in and clinical status of this population. The prevalence of antimuscarinic PIM use in this study cohort was high but consistent with other studies of community‐dwelling elderly adults, which have identified PIM prevalence ranging from 20% to 40% . In a recent study, the prevalence of PIM use in a general sample of Medicare Advantage Prescription Drug beneficiaries was 31.9% .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, approximately 30% of members who did not meet the definition of PIM use at the time of initiation of an antimuscarinic OAB treatment had medication use or a diagnosis that would be considered indicative of PIM use after initiation of OAB antimuscarinic treatment, demonstrating the dynamic nature of medication regimens in and clinical status of this population. The prevalence of antimuscarinic PIM use in this study cohort was high but consistent with other studies of community‐dwelling elderly adults, which have identified PIM prevalence ranging from 20% to 40% . In a recent study, the prevalence of PIM use in a general sample of Medicare Advantage Prescription Drug beneficiaries was 31.9% .…”
Section: Discussionsupporting
confidence: 90%
“…To minimize PIM use, providers should consider medical history and concurrent medication use when initiating OAB medication treatment. PIM use is generally associated with more prescribers being involved in an individual's care and more medications being taken . In clinical situations in which cognitive impairment may be intrinsic to the presentation, the patient may not be a reliable informant of current or past medication history.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of use of PIMs was close to that in a previous study . Some of these medications prolong hypoglycemia in individuals with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 44%
“…Moreover, the prevalence in different populations may vary according to the time and place of data gathering 13. As such, factors like ethnicity, economic incomes, and duration of data gathering may also contribute toward the differences 27,28…”
Section: Discussionmentioning
confidence: 99%